Effect of current density on composition and structure of electrodeposited Au-Ni alloy coatings. (1st July 2013) - Monev, M; Pfund, A; Beck, G; Petrov, K; Bretzler, R; Heuberger, U; Zielonka, A
Abstract : The effect of current density on composition and structure of galvanic Au-Ni alloy coatings electrodeposited from weakly acidic additive free electrolyte was investigated. At low current density (up to ∼10 mA cm −2 ), light yellow coloured alloys enriched with Au are deposited. At higher current density the Ni content is abruptly increased and the coatings become coarse and dark. Deposits with an average content of Ni up to ∼50 at-% were obtained. Only a small amount of Ni (up to 20 at-%) takes part in the formation of non-equilibrium super saturated Au-Ni solid solution. The remainder of the Ni is deposited in the interglobular space as an amorphous Ni oxide-hydroxide or as Ni bearing hydroxide salts. Besides Ni, the alloy coatings contain C, N, O, K and H.